Frame analysis and deviance scholarship: exploring links through drugs and guns - Zozula, Christine (Deviant behavior, 2020)
Deviance scholarship and social movement scholarship share similar substantive interests such as changes to rules and laws, identity-based movements, and a focus on social change. This article contends that social movement scholarship, particularly frame analysis, offers conceptual tools that may reinvigorate deviance scholarship and address some areas of concern raised by critics. Furthermore, this article explores the utility of the sociology of deviance for social movement scholarship by way of its focus on social control. It examines political action around two issues, opioid use and overdose deaths and gun-related deaths, highlighting the frames in each movement as either medicalizing or criminalizing (and sometimes both). Through these examples, this article considers the unique vantage point of deviance scholarship when considering social movement frames and discusses the potential harms of hybridized medical-legal discourses.